THE USE OF DIGITAL MEDIA IN PHYSICAL EDUCATION: A Sport Pedagogical and Media Pedagogical Challenge? - Greve, Steffen; Thumel, Mareike; Jastrow, Florian; Süßenbach, Jessica (Routledge Handbook of Digital Technologies in Sport, Exercise and Physical Education, 2025)
Usually, two central tasks are attributed to Physical Education (PE). On the one hand, students are to be enabled and encouraged to do sport throughout their lives, giving sport its own personal sense of purpose. On the other hand, students should be educated through sport, i.e. PE should impart values and develop educational potential. Digital media, which are omnipresent in students’ lives, have an enormous influence on schools as educational institutions. Learning with and about media has thus become a cross-cutting task for all subjects. In the context of PE, this means that learning processes can be supported by digital media (e.g. learning technical and tactical elements using video feedback). Equally, students should also learn what influence digital media can have on their sporting activities (e.g. what happens to personal data when young people use a fitness app). This chapter examines these areas of tension of contemporary media on the educational mandate of PE and the influences of life outside of school. In this context, sport pedagogical and media pedagogical axioms are related to each other and discussed. It is shown how PE can fulfil this task of media education without neglecting its two central tasks.
CRIS-Team Scopus Importer:2025-11-28